2020
DOI: 10.3390/ijms21207615
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MiRNA-195-5p and -451a in Diabetic Patients with Transient and Acute Ischemic Stroke in the Emergency Department

Abstract: (1) Background: Circulating micro-RNAs (miRNAs) modulate the expression of molecules in diabetes. We evaluated the expression of serum miRNA-195-5p and -451a in diabetic patients with ischemic stroke and correlated them with two markers of brain tissue integrity. (2) Methods: Seventy-eight subjects with acute ischemic stroke (AIS) or transient ischemic attack (TIA) (40 with diabetes) were enrolled. Serum miRNA levels, brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor A (VEGF-A) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…They also contribute to the development of DCM by regulating oxidative stress, in ammation, cardiomyocyte apoptosis, and mitochondrial function 2 . Previous study has reported that miRNA-195 inhibitors can reduce diabetic myocardial hypertrophy and improve cardiac function by reducing oxidative damage, inhibiting cell apoptosis, and promoting angiogenesis 30 . Moreover, miRNAs are involved in the regulation of multiple biological functions in the mitochondria by binding to their target genes 31 .…”
Section: Discussionmentioning
confidence: 99%
“…They also contribute to the development of DCM by regulating oxidative stress, in ammation, cardiomyocyte apoptosis, and mitochondrial function 2 . Previous study has reported that miRNA-195 inhibitors can reduce diabetic myocardial hypertrophy and improve cardiac function by reducing oxidative damage, inhibiting cell apoptosis, and promoting angiogenesis 30 . Moreover, miRNAs are involved in the regulation of multiple biological functions in the mitochondria by binding to their target genes 31 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of recent research, miR-451a and miR-195-5p were found to be upregulated in diabetic patients after a transient ischemic attack in comparison to control patients and non-diabetic patients after a transient ischemic attack[ 106 ]. The earlier study also demonstrated an increased expression level of miR-451a in the serum of subjects with ischemic stroke[ 107 ].…”
Section: Epigenetic Mechanisms Involved In Macrovascular Disease In Diabetic Patientsmentioning
confidence: 99%
“…Elevated levels of matrix metalloproteinase (MMP)-9 are associated with infarct growth and hemorrhagic transformation in patients admitted with acute ischemic stroke [8], whilst lower levels are associated with a better pre-stroke collateral status [9]. Whilst serum vascular endothelial growth factor (VEGF) levels were lower in patients with TIA or AIS [10], elevated VEGF levels were associated with larger infarct volume, post stroke cognitive impairment [11] and poorer outcome [12]. Although, a recent systematic review and meta-analysis has shown no association between serum VEGF levels and outcomes in ischemic stroke [13].…”
Section: Introductionmentioning
confidence: 99%